THE EFFECT OF DEXMEDETOMIDINE AS AN ADJUVANT TO ROPIVACAINE FOR WOUND INFILTRATION IN PROVIDING POSTOPERATIVE ANALGESIA FOR OPEN ABDOMINAL SURGERIES (Asian Journal of Medical Research and Health Sciences, 2026)
Background:  Wound infiltration with local anaesthetics is one of the multimodal approach to control post-operative pain after open abdominal surgeries. Aim and Objectives: The aim of the study is to evaluate the efficacy of wound infiltration with two different doses of dexmedetomidine added to ropivacaine on postoperative analgesia in patients undergoing open abdominal surgeries. Primary outcomes were magnitude of pain assessed by Numerical Rating Scale (NRS) at 0, 2, 4, 6, 12, 24 hours after surgery, time to first request of analgesia, analgesic requirement in the postoperative period over 24hours. Methods: 99 patients posted for elective open abdominal surgeries were randomly assigned to three groups. Group R received 30ml of 0.75% ropivacaine, GroupRD1 received 30ml of 0.75%ropivacaine with dexmedetomidine 0.5mcg/kg, GroupRD2 received 30ml of 0.75% ropivacaine with dexmedetomidine 1mcg/kg. Study drugs were made into equal volume of 60ml each by adding 0.9% normal saline and the study drug was infiltrated into the edges of the wound at the end of surgery. Results: The NRS scores for pain intensity did not show any statistical significance at any of the predefined time points. Time to first request of analgesia was longer in groupRD2 (136.2 +114.4 minutes) when compared to other groups (R, 66.06 + 58.5 minutes; RD1, 103.2+ 48.8 minutes; P < 0.05). Total amount of rescue fentanyl consumed in group RD2 (280.4 + 140.7 micrograms) was less when compared to RD1 (306.6 +133.8micrograms) R (331.8+ 99.2 micrograms); P=0.262). Conclusions: We conclude that wound infiltration with dexmedetomidine at both the doses (0.5mcg/kg and1mcg/kg) provides extended postoperative pain relief when administered along with 30ml of ropivacaine (0.75%). The pain relief provided by dexmedetomidine (1mcg/kg) appears to be superior to both dexmedetomidine (0.5mcg/kg) and plain ropivacaine.